2004
DOI: 10.1152/ajpheart.00592.2004
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-seryl-aspartyl-lysyl-proline stimulates angiogenesis in vitro and in vivo

Abstract: N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP), a natural inhibitor of pluripotent hematopoietic stem cell proliferation, has been suggested as capable of promoting an angiogenic response. We studied whether Ac-SDKP stimulates endothelial cell proliferation, migration, and tube formation; enhances angiogenic response in the rat cornea after implantation of a tumor spheroid; and increases capillary density in rat hearts with myocardial infarction (MI). In vitro, an immortal BALB/c mouse aortic endothelial 2210… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 40 publications
1
60
0
Order By: Relevance
“…Ac-SDKP also promotes angiogenesis (16). Our laboratory previously found that Ac-SDKP stimulated endothelial cell proliferation, migration, and tube formation in vitro and increased myocardial capillary density in vivo (41). This angiogenic property of Ac-SDKP may favorably provide blood flow and oxygen supply to the damaged myocardium, thus improving cardiac function.…”
Section: Discussionmentioning
confidence: 95%
“…Ac-SDKP also promotes angiogenesis (16). Our laboratory previously found that Ac-SDKP stimulated endothelial cell proliferation, migration, and tube formation in vitro and increased myocardial capillary density in vivo (41). This angiogenic property of Ac-SDKP may favorably provide blood flow and oxygen supply to the damaged myocardium, thus improving cardiac function.…”
Section: Discussionmentioning
confidence: 95%
“…57 N-Acetyl-Seryl-Aspartyl-Lysyl-Proline N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP or goralatide) is a potent natural inhibitor of hematopoietic stem cell proliferation that is degraded mainly by ACE. 58,59 In vitro, Ac-SDKP is a potent angiogenic factor 60 and inhibits collagen production by cardiac fibroblasts, 61 whereas in vivo, it blocks collagen deposition in the left ventricle of rats with hypertension or myocardial infarction. 62 ACE inhibitor treatment results in a significant increase in plasma Ac-SDKP levels in humans, 63 and in rats, the exogenous application of Ac-SDKP exerts many effects (including inhibition of Ang II-induced cell proliferation, left ventricular macrophage/ mast cell infiltration, and collagen deposition) that are generally associated with ACE inhibitor therapy.…”
Section: Angiotensin 1-7mentioning
confidence: 99%
“…Ac-SDKP, the product of T␤4 hydrolysis by meprin-␣ and POP, shares very similar properties with meprin-␣. It has been reported that Ac-SDKP promotes angiogenesis in cornea (43) and abdominal wall of the rat (26). The anti-inflammatory properties of Ac-SDKP have been shown in pathologies such as renal diseases, hypertension, and cardiovascular diseases (31,45).…”
Section: Discussionmentioning
confidence: 99%